2005
DOI: 10.1111/j.1525-1438.2005.15205.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review: re-treatment of patients with ovarian cancer with carboplatin after platinum resistance

Abstract: The objective of the analysis was to determine the effectiveness of re-treating patients with ovarian cancer, primary peritoneal cancer, and fallopian tube cancer with carboplatin after being deemed platinum resistant. From a database period January 1, 1996, to December 12, 2002, 34 patients were identified who received nonplatinum agents before resuming treatment with carboplatin. The median age was 65 years, and a median of two nonplatinum chemotherapy (range 1-5) prior to re-treatment with carboplatin was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…The merit of extending the PFI using a non-platinum agent at relapse, thereby reversing or partially reversing platinum resistance and improving the subsequent response to platinum, has been postulated based on previously reported trial data [22,23]. There are several mechanisms by which tumors develop resistance to platinum, including increased efflux, enhanced DNA repair of damage caused by the platinum agent, and defective cell death pathways [24,25].…”
Section: Emerging Strategy: Extending the Pfimentioning
confidence: 98%
“…The merit of extending the PFI using a non-platinum agent at relapse, thereby reversing or partially reversing platinum resistance and improving the subsequent response to platinum, has been postulated based on previously reported trial data [22,23]. There are several mechanisms by which tumors develop resistance to platinum, including increased efflux, enhanced DNA repair of damage caused by the platinum agent, and defective cell death pathways [24,25].…”
Section: Emerging Strategy: Extending the Pfimentioning
confidence: 98%
“…No other phase 3 studies of combination regimens versus single agents have reported clinical outcomes in partially platinumsensitive patients, but there are solid data from several phase 2 studies demonstrating that response to platinum retreatment is related to the length of prior response to platinum-based therapy [35]. It has been postulated that patients with partially platinum-sensitive ROC may benefit from a strategy of extending the platinum-free interval by use of a non-platinum agent, followed by a platinum-based regimen at subsequent relapse [39,41]. This hypothesis is being addressed in a current clinical trial, INNOVATYON, where patients with partially platinum-sensitive ROC will be randomized to either trabectedin with PLD or carboplatin with PLD.…”
Section: Platinum-sensitive Settingmentioning
confidence: 98%
“…After approval by the Institutional Review Board of the institution, a total of 28 patients with Pt-R ROC treated with CPT-Pt at the National Defense Medical College Hospital (Tokorowaza, Japan) between January, 2002 and December, 2012 were identified from a retrospective review of medical charts. All patients received combination therapy with TC as the first-line chemotherapy, and received CPT-Pt for the treatment of recurrent tumors with Pt-R. Platinum-resistance was sub-classified as follows (14,20): i) Platinum-refractory, patients who relapsed during TC therapy; ii) primary platinum-resistance, patients who relapsed within 6 months after the primary TC therapy; and iii) secondary platinum-resistance, patients who relapsed within 6 months after the second-line therapy with platinum-based regimen for the first relapse following primary TC therapy. From 2007, other regimens aside from five-day CPT-P were selected by clinicians according to kidney function and history of allergic reactions.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, dose-dense weekly administration of platinum agents has been reported to extend PFS for Pt-R ROC in recent years (12,13). Additionally, patients with Pt-R ROC may benefit again from platinum-based chemotherapy following the longer interval until platinum re-treatment with non-platinum single agents (14). Therefore, by modified method or timing of platinum administration, platinum re-treatment is potentially effective for Pt-R ROC.…”
Section: Introductionmentioning
confidence: 99%